Achieving Social Impact : Sociology in the Public Sphere - Soler Gallart, Marta (Springer International Publishing : Imprint: Springer, 2017)
This book presents the findings of research projects conducted by CREA (Community of Researchers on Excellence for all), a research community based in Barcelona, showing how social transformation combines scientific excellence with the political and social impact of the research. Analyzing the impact of pursuing social sciences research by providing examples of achievements and opportunities despite barriers and obstacles encountered along the way, it is of interest for a broad spectrum of scholars from the field of social sciences - particularly public sociology - as well as from other sciences such as biology and neuroscience.
Keywords: Social sciences.; Globalization.; Social structure.; Social inequality.; Economic development.; Social change.; elektronické knihy; electronic books